Human security, social stigma, and global health: the COVID-19 pandemic in Indonesia - Hastoro Dwinantoaji; Sumarni DW (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Coronavirus disease 2019 (COVID-19) is now a global public health threat with many medical, ethical, economic, and socialimpacts. COVID-19 has spread worldwide, to many Asian and Middle Eastern countries, the United Statesof America, and European countries. The current COVID-19 pandemic that has devastated Indonesia, has infected and killed more healthcare workers, in particular doctors and nurses, than any other outbreak in the history of this virus. People have basic needs that must be met for them to feel safe and secure. A history of the outbreak of the COVID-19 is brifley showed, before exploring the impact the virus had in Indonesia. During this exploration, some of the key issues arising from the experiences in Indonesia, in addressing the threat of COVID-19 will be reviewed. Drawing on the COVID-19 as the case study, we consider the ways in which the concept of human security expands understanding of its relationship to health. Further, weshow how major public health issues can evolve into security threats.The final section of the article will be an analysis of the lessons learned from COVID-19 and policy implications in addressing health and human security threats.